Cymbopogon citratus essential oil: effect on polymicrobial caries-related biofilm with low cytotoxicity - Oliveira, Maria Alcionéia Carvalho de; Borges, Aline Chiodi; Brighenti, Fernanda Lourenção; Salvador, Marcos José; Gontijo, Aline Vidal Lacerda; Koga-Ito, Cristiane Yumi (FapUNIFESP (SciELO), 2017)
The objective of this study was to evaluate the effects of Cymbopogon citratus essential oil and its main compound (citral) against primary dental colonizers and caries-related species. Chemical characterization of the essential oil was performed by gas chromatography/mass spectroscopy (GC/MS), and the main compound was determined. Antimicrobial activity was tested against Actinomyces naeslundii, Lactobacillus acidophilus, S. gordonii, S. mitis, S. mutans, S. sanguinis and S. sobrinus. Minimum inhibitory and bactericide concentrations were determined by broth microdilution assay for streptococci and lactobacilli reference, and for clinical strains. The effect of the essential oil on bacterial adhesion and biofilm formation/disruption was investigated. Negative (without treatment) and positive controls (chlorhexidine) were used. The effect of citral on preformed biofilm was also tested using the same methodology. Monospecies and microcosm biofilms were tested. ANOVA or Kruskal-Wallis tests were used (α=0.05). Cytotoxicity of the essential oil to human keratinocytes was performed by MTT assay. GC/MS demonstrated one major component (citral). The essential oil showed an inhibitory effect on all tested bacterial species, including S. mutans and L. acidophilus. Essential oil of C. citratus (10X MIC) reduced the number of viable cells of lactobacilli and streptococci biofilms (p < 0.05). The essential oil inhibited adhesion of caries-related polymicrobial biofilm to dental enamel (p < 0.01). Citral significantly reduced the number of viable cells of streptococci biofilm (p < 0.001). The essential oil showed low cytotoxicity to human keratinocytes. Based on these findings, this study can contribute to the development of new formulations for products like mouthwash, against dental biofilms.